Role of MR Enterography in Evaluation of Disease Activity in Pediatric Crohn’s Disease: Correlation between MR Enterography and Pediatric Crohn’s Disease Activity Index Scores - Radhakrishnan, Shilpa; Chellathurai, Amarnath; Sankaranrayanan, Srinivas; Sankar, Dharani; Rajan, Suja (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Objectives The aim of the study was to assess the role of MR Enterography (MRE) in the diagnosis and follow-up of children with Crohn’s disease (CD) and to correlate disease activity indices with known MRE features of active disease.Methods This was a retrospective study including 24 patients (median age 11 years, 17 males) with clinically and histologically proven CD who underwent MRE. Two previously validated MRE scores—Magnetic Resonance Enterography Global Score (MEGS) and CD MRI index (CDMI)—were calculated. A correlative analysis was made between the Pediatric Crohn’s Disease Activity Index (PCDAI) score and MRE scores as well as individually with each MR variable. Comparison of both the MR scores was made between patients with different disease activity.Results MEGS and PCDAI scores showed strong positive correlation (r = 0.724, p = < 0.001); CDMI and PCDAI scores showed moderate positive correlation (r = 0.661, p = 0.0004). There was statistically significant difference in the MR scores between patients grouped by clinical activity. Among individual MR variables, mural thickness and enhancement best predicted the disease activity.Conclusions MRE-based scores and findings correlate with clinical activity in pediatric CD. Thereby, MRE can be considered a valuable tool in the management of CD, predicting disease activity and offering a potential alternative to endoscopy in monitoring patients during follow-up.
Keywords: CD MRI index; Crohn’s disease; MR enterography global score